2002
DOI: 10.1007/s11661-002-0161-y
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic threshold stress intensity factor, KIH and crack growth rate in delayed hydride cracking of Zr-2.5Nb pressure tubes

Abstract: The objectives of this study are to systematically investigate the delayed hydride cracking (DHC) velocity and the threshold-stress intensity factor, K IH , of a Zr-2.5Nb pressure tube as a function of orientation and elucidate the cause of this anistropic DHC behavior. The DHC velocity as a function of orientation was determined using flattened cantilever beam specimens with 60 ppm H while the threshold-stress intensity factor K IH , was evaluated as a function of orientation on the curved compacttension (CT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 12 publications
2
31
0
Order By: Relevance
“…4) even in the same cracking plane with the same stress being applied. Since it was demonstrated that the yield strengths of the CANDU Zr-2.5Nb tube are almost the same in both directions [5], Eq. (2) shows that the anisotropic DHCV depends only upon hydrogen diffusion and K IH with the orientation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4) even in the same cracking plane with the same stress being applied. Since it was demonstrated that the yield strengths of the CANDU Zr-2.5Nb tube are almost the same in both directions [5], Eq. (2) shows that the anisotropic DHCV depends only upon hydrogen diffusion and K IH with the orientation.…”
Section: Resultsmentioning
confidence: 99%
“…By demonstrating a larger extent of the textural change and higher strain hardening after yielding in the axial direction of a CANDU Zr-2.5Nb pressure tube when compared to that in the radial direction, Kim suggested that a steeper stress gradient ahead of the crack tip in the axial direction is the cause of an anisotropic DHCV with orientation [5]. However, his hypothesis has some defects because it was suggested based on the previous DHC models.…”
Section: Introductionmentioning
confidence: 97%
“…17 mm compact tension (CT) and cantilever beam (CB) specimens were used to measure the CGR in the axial and radial directions of the Zr-2.5Nb tube [17]. These specimens were pre-charged to 6-100 ppm of hydrogen using an electrolytic method followed by homogenization treatments and then pre-fatigued to introduce a 1.7 mm fatigue crack.…”
Section: Methodsmentioning
confidence: 99%
“…A study by Kim et al (2002) attributed the difference between longitudinal and throughthickness crack velocities to anisotropy of the stress gradient ahead of the crack tip.…”
Section: Stress Gradient Anisotropymentioning
confidence: 99%
“…Stage 2) Stable crack growth, having little rate change with increase in K I . Stage 3) The onset of unstable cracking when K IC is reached ....................................................................................................................................... 25 Figure 17 -Schematic diagram of the stress field at a flaw .. ........................................................................ 26 Figure 18 -Use of Tresca criterion to predict plastic zone size and stress gradient [Bell 2001] ................. 27 Figure 19 -Schematic diagram of cantilever beam specimens from flattened pressure tube [Kim 2002] .... 29 Figure 20 -DHC velocity of flattened pressure tube cantilever beam specimens with cracking from 170 °C to 270 °C ....................................................................................................................................................... 30 Figure 21 -Strain hardening in the radial and longitudinal directions ( =(UTS-YS)/YS ) as a function of 1/T 31 Figure 22 -Steeper stress gradient ahead of the crack tip in the longitudinal direction of the pressure tube than the radial direction [Kim 2001] ...................................................................................... 31 Figure 23 -The effect of temperature on DHC velocity in the axial (a) and radial (b) directions [Jovanovic 2001] ............................................................................................................................................................. 35 Figure 24 -Ratio of the DHC velocities as a function of temperature for specimens annealed at 1*, 24, and 1000 hours at 400 °C. *For β-phase decomposition, 36 h at 300 °C equates to 1 h at 400 °C [Jovanovic 2001] ............................................................................................................................................................. 35 Figure 25 -Effect of grain size on time to fracture at several stress intensities [Coleman 1979] ................ 38 Figure 26 -Axial and radial crack velocities at 130 °C in quenched and aged 'KANUPP' pressure tubes compared to axial and radial velocity confidence limits in cold-worked pressure tubes [Cheadle 1996] .... 39 Figure 27 -A through-wall crack at two rolled joints in and Pickering 4 (b).…”
mentioning
confidence: 99%